Correlation between Academic Stress and Type of Premenstrual Syndrome In 3rd Semester Female Medical Students of Sebelas Maret University - Anggaresti, Annisa Permatasuhdan; ., Indriyati .; Timor, Amandha Boy (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Background: Premenstrual syndrome is a common health problem that most reported in productive age women. One of the influence factors the occurrence of premenstrual syndrome is stress. Activities and high academic demands in the college students will lead to physical fatigue, mental fatigue and academic stress. The aim of this study is to identify the correlation between academic stress and premenstrual syndrome in 3rd semester female medical students of Sebelas Maret University. Methods: This study is observational analytic research with cross sectional approach. The study sample is 3rd semester female medical students of Sebelas Maret University. Subjects fill out questionnaires of academic stress and premenstrual syndrome. Sampling was done by purposive random sampling after selected based on inclusion and exclusion criteria. 117 data samples were collected, and the data were analyzed using Chi-square test and Kolmogorov-Smirnov test. Result: Based on data analysis, there is no significant correlation between academic stress and premenstrual syndrome in 3rd semester female medical students of Sebelas Maret University with p valueÂ =Â 0,929 (p > 0,05). Conclusion: Statistically, there is no significant correlation between academic stress and premenstrual syndrome in 3rd semester female medical students of Sebelas Maret University. Keywords: Academic Stress, Premenstrual Syndrome, Medical StudentsÂ